1999
DOI: 10.1128/aem.65.2.472-476.1999
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Analysis of Escherichia coli Strains Isolated from Children and Chickens Living in Close Contact

Abstract: Escherichia coli isolates from rectal swabs from 62 chickens and stools from 42 children living in close contact with chickens on the same farms in Kiambu district, Kenya, were compared for their genetic relatedness. Antibiotic susceptibility profiles broadly categorized isolates from the children and from the chickens into two separate clusters: the majority (144; 85.5%) of the E. coli isolates from children were multidrug resistant, while the majority (216; 87.1%) of the E. coli isolates from chickens were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 15 publications
(11 reference statements)
1
21
1
1
Order By: Relevance
“…In the studies conducted in Africa, Kariuki et al. () concluded that although several different pulsed‐field gel electrophoresis genotypes of E. coli were isolated from children and chickens from the same farms in Kenya, the E. coli strains from these two sources were distinct. Rwego et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies conducted in Africa, Kariuki et al. () concluded that although several different pulsed‐field gel electrophoresis genotypes of E. coli were isolated from children and chickens from the same farms in Kenya, the E. coli strains from these two sources were distinct. Rwego et al.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst animal faeces in food or water is a matter of current concern in developed countries, they may be of less relative importance in areas where human faeces are disposed of inadequately. Though similar pathogens can be identified in animals and man, there may be less cross‐infection than previously thought, as recent genotyping studies suggest ( Kariuki et al . 1999 ).…”
Section: Introduction: Clearing Away the Fogmentioning
confidence: 91%
“…Other molecular procedures, such as random amplified polymorphic DNA analysis (1), have recently been developed for fingerprinting microbial genomes. The potential to identify individual strains of different bacteria by genetic profiles indicates that molecular approaches may also be suitable for source differentiation of fecal bacteria (3,8).…”
mentioning
confidence: 99%